Dominant ideologies in Irish educational-thought - consensualism, essentialism and meritocratic individualism - Lynch, Kathleen (Economic & Social Studies, 1987)
Through the analysis of the works of Irish (the analysis is confined to the Republic of Ireland) educationalists (over the last 30 years) three prominent ideological paradigms are evident in the literature. The first of these involves a particular conception of society itself (consensualism), the second involves a particular conception of the individual (essentialism), while the third involves a particular conception of the relationship of the individual to society (meritocratic individualism). The paper will begin with a brief discussion of the research procedure, and the concept of ideology. The main part of the paper will be divided into two sections. The opening section will be devoted to identifying the existence of the various ideologies in educational literature and discussing their implications and interrelationships. The second part of the paper will attempt to explain why educational intellectuals in Ireland have adopted these particular paradigmatic assumptions.
Keywords: Education - Ireland; Sociology